The Text-Critical Utility of the Peshitta to Ezekiel in View of Recent Research - Mushayabasa, Godwin (Vetus Testamentum, 2017)
Following recent studies demonstrating that the Peshitta to Ezekiel is largely a translation that was rendered at the level of semantic frames or the idiomatic level, the logical question to be asked from the point of view of textual criticism of the Hebrew Bible is whether such a translation would be useful at all within that discipline. Traditionally, a version that is considered ideal and useful for the textual criticism of the Bible is one whose translation technique is as literal as possible. Studying some difficult texts in the light of the idiomatic approach in pe shows that pe can still provide meaningful contribution to the text-critical study of the book of Ezekiel, though not in every instance. There are instances where the process of translation in pe could have made the base text difficult to retrace. pe can therefore be used in the study of Ezekiel, with some precautions.